UPAYA PENGUATAN PROGRAM STIMULASI, DETEKSI DAN INTERVENSI DINI TUMBUH KEMBANG (SDIDTK) MELALUI PEMERIKSAAN ANTROPOMETRI PADA ANAK PRASEKOLAH - Rahayu, Suci Fitri; Anggeriyane, Esme; Mariani, Mariani (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2021)
The importance of paying attention to nutritional status in early childhood is useful for maximizing the growth phase of early childhood. One way to assess nutritional status for early childhood can be assessed by means of anthropometric measurements. Anthropometric measurements are measurements of various dimensions and body compositions of various ages, such as baby length, head circumference, height, weight, chest circumference, and upper arm circumference. TK Aisyiyah 15 Bustanul Athfal Banjarmasin is one of the schools that has not implemented early detection of the growth and development of pre-school children because the teachers do not understand how to examine and document the results of the examination. Efforts to strengthen the Stimulation, Detection and Early Development Development Program (SDIDTK). Methods ranging from FGDs, training and mentoring so that teachers acquire comprehensive skills in anthropometric examinations. The activity was carried out in August and was continued with mentoring for teachers to be able to monitor and evaluate activities. The results of activities in efforts to strengthen stimulation, detection and early intervention programs for growth and development produce skills for teachers in conducting anthropometric examinations and screening children's growth and development. Efforts to strengthen the program of stimulation, detection and early intervention for growth and development can increase teachers' knowledge in conducting anthropometric examinations and growth screening.